Mudjair: Intellectual Progress and Fisheries Innovation in the Dutch Colonial Period - Alfahmi, Moch Nizam; Wahyudi, Deny Yudho; Hariyono, Hariyono; Ashari, Gedhe (Program Studi Pendidikan Sejarah FKIP Universitas Mulawarman, 2024)
Several historical studies that exist today have reviewed how the fishing industry developed during the colonial period. However, generally existing studies focus more on aspects of marine and port fisheries. The inland or freshwater fisheries aspect is not highlighted much. One of the results of the development of inland fisheries knowledge and technology is the innovation of mudjair fish. This paper tries to dig deeper into the innovators of mudjair fish both in terms of background knowledge and domestication methods. The method used in this paper is the historical method. Based on the results of the study, Mudjair's knowledge as an innovator is based on informal knowledge. The series of fish domestication processes he used were scientific organic knowledge. This is evidence of intellectual progress and innovation in the field of fisheries.